A geological and geophysical crustal section across the Magallanes–Fagnano fault in Tierra del Fuego - Tassone, Alejandro (2005)
Geophysical and geological field surveys carried out in the central and eastern part of the Argentinean Tierra del Fuego Island on the Magallanes–Fagnano fault system (MFS) delineate its main structural features and tectonic setting. Gravity and magnetic data provide critical information for those areas lacking good exposures and support a present-day transtensional tectonic regime for the MFS. In the surveyed area, the MFS segments have a clear morphological expression and are associated with localized gravity minima interpreted as pullapart basins. In the southeastern corner of Lago Fagnano, the magnetic data suggest a prominent crystalline body in the subsurface, partially exposed in Cerro Hewhoepen. The shape and position of this intrusive body suggest that its emplacement was localized in a releasing bend. Two-dimensional density modeling along a 40 km long N–S section east of Lago Fagnano suggests a deep duplex similar to that exposed in the western part of the island. The obtained model, combined with available surface data, implies the subsurface configuration of geological units and structures, in which the structure of the deep duplex is similar to that exposed in the western part of the Island. The model indicates the southward deepening of the basement from 5 to 7 km and provides further support for the piston shape of the Hewhoepen intrusive.